PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KETEREMPILAN BERPIKIR KRITIS SISWA PADA MATERI JAMUR (FUNGI) KELAS X - Meilianti, Dasni Elsa; Sayuti, Irda; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Limitations on the material used in learning there needs to be a development of teaching materials which one of them is in the form of learning module. The purpose of this research is to develop learning module based scientific approach to improved the skills of critical thinking of students to the matter fungi a class X. Of research in successor program study education biology of PMIPA FKIP University of Riau and SMAN 1 Pekanbaru in February-May 2016. The kind of research this is research of development by use the model ADDIE was done to the stages of development. An instrument data collection in this research is sheets of assessment/validation modules, students chief response and sheets of the answer students. After module developed, we do testing I in 15 students second semester education biology FKIP UR. Next validated by 4 people validator and testing II in 20 people school tuition class x in SMAN 1 Pekanbaru. The results of validation show a score a whole module obtain the average score 4.14 to a category valid. Consisting of the aspect of content that served with the average score 4.19 category valid, aspects language score was obtained 4.12 to a category valid, next on the aspect of cereal offering have a score 4.15 category valid and facets kegrafisan obtain the average score 4.12 category valid. The results of testing I shows the average value 90 to a category very good. The results of testing II show a score rerata successive is 81 and 80 to a category good. The results of the analysis answer school tuition in learning module 1 shows value 78 category good. Learning module based scientific approach can improved the skills of critical thinking of students and useful for used in learning.Keywords: development, Module, Scientific, Critical thinking, Fungi